Implementation of daily chlorhexidine bathing in intensive care units for reduction of central line-associated bloodstream infections. (April 2021) - Scheier, T.; Saleschus, D.; Dunic, M.; Fröhlich, M.R.; Schüpbach, R.; Falk, C.; Sax, H.; Kuster, S.P.; Schreiber, P.W.
Summary: Background: Daily chlorhexidine bathing has been associated with a reduction in central line-associated bloodstream infections (CLABSI). In the setting of an already established CLABSI surveillance system and an implemented CLABSI prevention bundle, we analysed the effect of daily chlorhexidine bathing in ICU patients on CLABSI incidence and its causative pathogens. Methods: This was a before-and-after study in intensive care units (ICUs) at a tertiary-care centre in Switzerland. Prospective surveillance of CLABSIs and their aetiologies was established. The intervention consisted of daily chlorhexidine bathing of ICU patients with a central venous catheter. A baseline period of 19 months was followed by an intervention period of 9 months. Findings: A total of 5008 patients were included. In the baseline period a mean CLABSI rate of 2.45/1000 catheter days (95% confidence interval (CI) 1.93–3.07) was observed, followed by 1.00/1000 catheter days (95% CI 0.55–1.67; P <0.001) in the intervention period. Introduction of chlorhexidine bathing was independently associated with a reduced risk of CLABSI (adjusted odds ratio 0.47, 95% CI 0.26–0.84, P =0.011). We did not observe a significant change in aetiology except for an increase of Serratia marcescens in the intervention period. Conclusions: Introduction of daily chlorhexidine bathing resulted in a decline in CLABSI incidence on ICUs. Starting from a baseline CLABSI rate that can be considered standard in a high-income setting and several measures for CLABSI prevention implemented, chlorhexidine bathing proved helpful for a further reduction.